Leaching and heating process as alternative to produce fish protein powder from Kilka (Clupeonella cultiventris caspia) - KAVEH RAHMANIFARAH; BAHAREH SHABANPOUR; AMIR REZA SHAVIKLO; NEHRAN AALAMI (Smujo International, 2014)
Abstract. Rahmanifarah K, Shabanpour B, Shaviklo AR, Aalami M. 2014. Leaching and heating process as alternative to produce fish protein powder from Kilka (Clupeonella cultiventris caspia). Nusantara Bioscience 6: 1-6. The effect of protein extraction procedures (leached mince and heated suspension) on selected properties of fish protein powder (proximate composition, pH, color, density, viscosity, fat adsorption, emulsifying capacity, emulsifying stability, foaming capacity, foaming stability, WBC, protein solubility in water, hygroscopicity, Trichloroacetic acid (TCA)-soluble peptides and free sulfhydryl groups) was investigated. Results showed that Fish protein powder (FPP) produced by leaching mince (LM) have higher protein, moisture, ash, pH, L*, viscosity, emulsion capacity, emulsion stability, foam capacity, foam stability, water binding capacity (WBC), protein solubility, hygroscopicity, TCA soluble peptides and free sulfhydryl group content than heated suspension (HS) (P<0.05). However, HS had higher fat and density in comparison with LM (P<0.05). No significant differences between a*, b* and fat adsorption were observed (P>0.05). Overall, it was observed that high temperature during heating of suspension in HS method makes possible protein denaturation and aggregation. Consequently, based on functional, chemical and physical properties, extraction of fish protein by leaching process was found to be suitable for the production of fish protein powder.